Complexities of care: Common components of models of care in geriatrics. Issue 7 (29th April 2022) - McNabney, Matthew K.; Green, Ariel R.; Burke, Meg; Le, Stephanie T.; Butler, Dawn; Chun, Audrey K.; Elliott, David P.; Fulton, Ana Tuya; Hyer, Kathryn; Setters, Belinda; Shega, Joseph W.
Abstract: As people age, they are more likely to have an increasing number of medical diagnoses and medications, as well as healthcare providers who care for those conditions. Health professionals caring for older adults understand that medical issues are not the sole factors in the phenomenon of this "care complexity." Socioeconomic, cognitive, functional, and organizational factors play a significant role. Care complexity also affects family caregivers, providers, and healthcare systems and therefore society at large. The American Geriatrics Society (AGS) created a work group to review care to identify the most common components of existing healthcare models that address care complexity in older adults. This article, a product of that work group, defines care complexity in older adults, reviews healthcare models and those most common components within them and identifies potential gaps that require attention to reduce the burden of care complexity in older adults.